Spin conductivity of the two-dimensional anisotropic frustrated Heisenberg model in the honeycomb lattice. (July 2016) - Lima, L.S.
Abstract: We use the SU(3) Schwinger׳s boson theory to study the spin transport properties of the two-dimensional anisotropic frustrated Heisenberg model in a honeycomb lattice at T =0. We have investigated the behavior of the spin conductivity for this model which presents a single-ion anisotropy and J 1 and J 2 exchange interactions. We study the spin transport in the Bose–Einstein condensation regime where we have that the t z bosons are condensed and the following condition is valid: 〈 t z 〉 = 〈 t z † 〉 = t . Our results show a metallic spin transport for ω > 0 and a superconductor spin transport in the limit of DC conductivity, ω → 0, where σ ( ω ) tends to infinity in this limit of ω . Abstract : Highlights: We have analyzed the honeycomb model. We use the Kubo formalism to calculate the spin conductivity using SU3 Schwinger boson. We have analyzed the spin transport properties of the model.